ANALISIS KETERSEDIAAN DAN KEBUTUHAN SARANA PRASARANA SOSIAL DI KECAMATAN MARISA, KABUPATEN POHUWATO - Umar, Indriani (Universitas Bina Taruna Gorontalo, 2025)
This study analyzes the availability and projected needs for social infrastructure in Marisa District for the period 2023-2035. The research methodology uses a quantitative descriptive approach with population projection techniques based on SNI 03-1733-2004 standards on Procedures for Urban Housing Environment Planning. The research findings indicate that for the period 2023-2025, Marisa Subdistrict requires additional educational infrastructure in the form of 8 kindergarten/RA units, 4 elementary school/MI units, and 1 high school/SMK/MA unit, as well as 2 doctor's practice units for the health sector. The 2035 projection indicates a greater need for 16 kindergarten units, 10 elementary/madrasah ibtidaiyah units, 3 senior high school/vocational school/madrasah aliyah units, and 4 doctor's clinics. Meanwhile, religious facilities are deemed adequate until 2035. Development priorities are focused on adding basic and upper secondary education facilities. This study provides strategic references for local governments in formulating policies for the development of social infrastructure, particularly in the fields of education and health. The implementation of the study's findings is expected to optimize development in Marisa Subdistrict, the capital of Pohuwato Regency, making it more effective and structured in line with regional needs.